Rat liver responsiveness to gluconeogenic substrates during insulin-induced hypoglycemia - de Souza,H.M. (2001)
Hepatic responsiveness to gluconeogenic substrates during insulin-induced hypoglycemia was investigated. For this purpose, livers were perfused with a saturating concentration of 2 mM glycerol, 5 mM L-alanine or 5 mM L-glutamine as gluconeogenic substrates. All experiments were performed 1 h after an ip injection of saline (CN group) or 1 IU/kg of insulin (IN group). The IN group showed higher (P<0.05) hepatic glucose production from glycerol, L-alanine and L-glutamine and higher (P<0.05) production of L-lactate, pyruvate and urea from L-alanine and L-glutamine. In addition, ip injection of 100 mg/kg glycerol, L-alanine and L-glutamine promoted glucose recovery. The results indicate that the hepatic capacity to produce glucose from gluconeogenic precursors was increased during insulin-induced hypoglycemia.